Foreign Investment in Ukraine: Types and Forms - Kossak, Volodymyr; Yanovytska, Halyna (International Journal of Criminology and Sociology, 2021)
An important condition for the transition to a market economy is the intensification of the investment process. Among other factors, attracting foreign investment is crucial. For their effective use, an appropriate regulatory framework for regulating the legal basis for their implementation is required. It is necessary to determine the range and legal status of foreign investors, types and forms of foreign investment, legal means of protection of the rights of foreign investors. At the same time, the mechanism of regulation and protection of foreign investments is influenced by the legal regime of investment, which is established by the national legislation of Ukraine. The article is devoted to the classification of types of foreign investment. Money, goods and corporate rights, intellectual property, rights in them and securities rights, requirements for the exploitation of natural resources as a form of foreign investment are considered. The legal regime of the listed types of foreign investments are analyzed in detail. The evolution of legislation in the field of foreign investment regulation is investigated. Knowledge on foreign investment, is a legal regime as comprehended. The directions of improvement of the mechanism of attraction of foreign investments by established privileges in taxation of profits of foreign investors, legal support of the investment process is highlighted. Prospects of foreign direction and sphere of investment state policy of Ukraine are analyzed.